Pengaruh Keaktifan Berorganisasi & Leadership Traits terhadap Kematangan Karir Anggota Keluarga Mahasiswa Lampung di Semarang - Damilu, Silfana; Awalya, Awalya (Institut Agama Islam Negeri Kerinci, Indonesia, 2025)
Career maturity among college students indicates their readiness to face life after graduation. Career maturity is defined as the extent to which individuals successfully complete specific career development tasks in accordance with their stage of development. This study aims to examine the influence of involvement in organizations and leadership traits on the career maturity of Kamapala members. This study uses a correlational quantitative method. The population of this study consists of 297 active Kamapala members who regularly participate in organizational activities. Kamapala members are students from various universities in Semarang, including Universitas Negeri Semarang, UIN Walisongo Semarang, Universitas Muhammadiyah Semarang, Universitas Martitim Amni Semarang, and Universitas Islam Sultan Agung Semarang. The conclusion of this study is that the level of organizational activeness, leadership traits, and career maturity of students is high if the value of organizational activeness is high, the results in this study show that there is a positive relationship between variables and in simultaneous analysis also identified a significant positive relationship between organizational activeness, leadership traits, and career maturity of students. This research is expected to contribute to the academic literature regarding the role of student organizations in personal and profesional development